PENGARUH LOKASI DAN KUALITAS PELAYANAN TERHADAP MINAT BELI KONSUMEN PADA PT. TRIYASA SUKSES MAKMUR MEDAN - Anto Tulim (LP2MTBM MAKARIOZ, 2019)
Consumer buying interest are influenced by the location and service quality factor. Companies must be able to choose a strategic location and provide good quality service towards consumers to beat others in competition. Location as a potential strategic weapon to beat competitors. Quality of service as an important factor to influence consumer buying interest. Strategic location and good service are able to increase consumer buying interest on the product selling. The purpose of this study is to find out or analyze the influence of location and quality of service towards consumer buying interest at PT. Triyasa Sukses Makmur Medan. This research was conducted at PT. Triyasa Sukses Makmur Medan. The type of research used is descriptive quantitative research.The results shows that the location variable and quality of service make a positive and significant influence both partially and simultaneously towards consumer buying interest at PT. Triyasa Sukses Makmur Medan. 37,1% of R Square value shows that 37,1% ability of location (X1) and quality of service (X2) variables are able to influence consumer buying interest (Y) at PT. Triyasa Sukses Makmur Medan while the remaining 62,9% are the influence of other independent variables that are not explained or not analyzed by researcher in this study such as product quality, product distribution or prices variables.